Early versus delayed removal of the pericardial drain in patients with cardiac tamponade complicating radiofrequency ablation of atrial fibrillation. (10th January 2020) - Zhao, Qianqian; Li, Linling; Liu, Nian; Zhang, Mengxia; Wu, Kui; Ruan, Yanfei; Bai, Rong; Du, Xin; Dong, Jianzeng; Ma, Changsheng
Abstract: Introduction: Cardiac tamponade is a common life‐threatening complication during radiofrequency ablation of atrial fibrillation (RAAF) and is mostly managed by pericardiocentesis. Thus far, the optimal timing for drain removal has not been established. Methods and Results: We retrospectively enrolled patients with cardiac tamponade complicating RAAF. The ablation was performed with interrupted novel oral anticoagulants, interrupted warfarin or uninterrupted warfarin protocols. An observation period of at least 30 minutes after the last aspiration via the drain was used to monitor the reaccumulation of pericardial fluid, and then, the patients were divided into an early removal (ER) group in the electrophysiology (EP) laboratory and a delayed removal (DR) group in the ward. A total of 51 patients were included: 25 patients in the ER group and 26 patients in the DR group. There were no significant differences in baseline demographics between the two groups, and no cardiac tamponade reoccurred in either group in the ward. Unlike the DR group, the ER group showed an association with a decreased rate of chest pain ( P  = .000), fever ( P  = .001), nausea ( P  = .000), in‐hospital recurrent AF ( P  = .010), and antibiotic use ( P  = .012). Anticoagulation was earlier ( P  = .009), and the median in‐hospital stay was shorter ( P  = .001) in the ER group than in the DR group. Conclusions: ER of the pericardial drain after no evidence of pericardial bleeding for at least 30 minutes in the EP laboratory is safe and associated with a better early hospital course.